Hey users
Provide me the answers of Question no.8
Attachments:
![](https://hi-static.z-dn.net/files/d5d/47b5f1665b590d48f2d552f0ffa3ce18.jpg)
Answers
Answered by
1
(1/sinx-sinx)*(1/cosx-cosx)*(sinx/cosx+cosx/sinx)
=(1-sin²x/sinx)*(1-cos²x/cosx)*(sin²x+cos²x/sinxcosx)
=cos²x/sinx*sin²x/cosx*1/sinx cosx
=1
plzzzzz mark as brainliest
=(1-sin²x/sinx)*(1-cos²x/cosx)*(sin²x+cos²x/sinxcosx)
=cos²x/sinx*sin²x/cosx*1/sinx cosx
=1
plzzzzz mark as brainliest
Answered by
4
qqqqqqppppppqpqpqpqp:
can u answer my last question
Similar questions